Conduct problems, hyperactivity, and screen time among community youth: can mindfulness help? an exploratory study - Kim, Soyeon; Munten, Stephanie; Kolla, Nathan J.; Konkolÿ Thege, Barna (Frontiers in Psychiatry, 2024)
Background: The influence of mindfulness-based intervention (MBI) programs on behavioural problems among community youth is largely understudied. While technology continues to evolve and the prevalence of screen-based activities is rising, limited studies have accounted for screen time when examining the efficacy of an MBI. Accordingly, this study investigated the impact of MBI on conduct problems and hyperactivity among community youth, accounting for sociodemographic characteristics and four types of screen time. Method: Linear regression models were used to investigate 1) the association between four types of screen time and behavioural problems (i.e., conduct problems and hyperactivity) and 2) the efficacy of online mindfulness programs in reducing behavioural problems among community youth. The data were collected at baseline, intervention completion and 1-month follow-up (Spring 2021 to Spring 2022) in Ontario, Canada (n=117, mean age=16.82, male=22%, non-White=21%). Results: The average score for conduct problems was within the normal range, while the average score for hyperactivity was considered borderline at baseline. Accounting for other types of screen time, time spent playing video games was significantly associated with increased conduct problems (β= 1.75, p=.03), albeit rendering non-significant after correcting for multiple comparisons. The online mindfulness program was significantly associated with reduced hyperactivity, controlling for baseline mental health, age, sex and screen time. Conclusion: The current findings suggest a 12-week online mindfulness program may play a positive role in reducing hyperactivity even when accounting for screen time. Our findings advocate the evidence base on the efficacy of MBI in managing hyperactivity.